Bioequivalence study of ticagrelor in normal, healthy Indian subjects under fasting conditions: A randomized, blinded, crossover study - PRADEEP, T. PAVAN; GATTU, RANJITH KUMAR; NARALASETTY, ANIL KUMAR; NADIG, SREEVATHSA; KUMAR, K. VINODH; KUMAR, N. RAVI; BIRLA, ASHISH; REVANKAR, SANTOSH Y (Heart India, 2023)
Objectives: The objectives of this study were to evaluate the bioequivalence and safety profiles of the test drug and reference drug of 90 mg ticagrelor tablets under fasting conditions. Methods: This was a randomized, blinded, balanced, two-treatment, two-period, two-sequence, single-dose, crossover bioequivalence study in normal, healthy adults. Subjects were randomized to receive a single dose of test or reference drug (ticagrelor 90 mg oral) under fasting conditions with a 16-day washout period. The primary pharmacokinetic variables were peak plasma concentration (Cmax), area under the plasma concentration (AUC) time curve measured to the last quantifiable concentration (AUCT), and time to maximum drug concentration (Tmax). Bioequivalence was concluded if 90% confidence intervals (CIs) of the geometric mean ratio of the test/reference drugs AUCT and Cmax are within the predefined range of 80%-125%. Adverse events (AEs) were also assessed. Results: Forty-two healthy adult males were enrolled, but 4 withdrew and 38 subjects successfully completed the study. There was no difference between the test and reference drugs regarding pharmacokinetic parameters. The median (range) Tmax was 1.67 h (1-4 h) and 2 h (1-4.5 h) for the test and reference products, respectively. The estimated 90% CIs of the geometric mean ratio for AUCT and Cmax satisfied the predefined bioequivalence criteria of 80%-125%. On analysis of variance, no significant "sequence" and "period" effects were observed for the pharmacokinetic parameters. No AEs were reported in the study. Conclusion: Our findings indicate that the test product is bioequivalent to the reference product and safe and well-tolerated in healthy Indian adults.